Developmental Origins of Health Inequality - Gabriella Conti; Giacomo Mason; Stavros Poupakis (Institute of Labor Economics (IZA), 2019)
Building on early animal studies, 20th-century researchers increasingly explored the fact that early events – ranging from conception to childhood – affect a child's health trajectory in the long-term. By the 21st century, a wide body of research had emerged, incorporating the original 'Fetal Origins Hypothesis' into the 'Developmental Origins of Health and Disease'. Evidence from OECD countries suggests that health inequalities are strongly correlated with many dimensions of socio-economic status, such as educational attainment; and that they tend to increase with age and carry stark intergenerational implications. Different economic theories have been developed to rationalize this evidence, with an overarching comprehensive framework still lacking. Existing models widely rely on human capital theory, which has given rise to separate dynamic models of adult and child health capital, within a production function framework. A large body of empirical evidence has also found support for the developmental origins of inequalities in health. On the one hand, studies exploiting quasi-random exposure to adverse events have shown long-term physical and mental health impacts of exposure to early shocks, including pandemics or maternal illness, famine, malnutrition, stress, vitamin deficiencies, maltreatment, pollution and economic recessions. On the other hand, studies from the 20th century have shown that early interventions of various content and delivery format improve life course health. Further, given that the most socioeconomically disadvantaged groups show the greatest gains, such measures can potentially reduce health inequalities. However, studies of long-term impacts, as well as the mechanisms via which shocks or policies affect health, and the dynamic interaction amongst them, are still lacking. Mapping the complexities of those early event dynamics is an important avenue for future research.
Keywords: I14; J13; J24; 330; developmental origins; health inequalities; early interventions; health production function; health economics